Glycosaminoglycans in components of the rabbit eye: synthesis and characterization - Goes, R. M.; Laicine, E. M.; Porcionatto, M. A.; Nader, H. B.; Haddad, A. (Swets Zeitlinger Publishers, 1999)
Purpose. To trace the eye components involved in proteoglycan synthesis and to characterize the sulfated glycosaminoglycans which are associated to these macromolecules.Methods. Sodium [S-35]-sulfate was injected intravitreally and the rabbits were killed at different time intervals after the injection. The glycosaminoglycans of choroid, ciliary body, cornea, iris, lens capsule, retina and sclera were extracted and processed for estimations of their specific activities, and for electrophoresis plus autoradiography with or without previous treatment with specific enzymes. In addition, methacrylate sections of the eyes were analysed by autoradiography.Results. The peak of specific activities of the glycosaminoglycans of all eye components occurred at 2 days after the intravitreal injection of [S-35]-sulfate. The autoradiography of the agarose gels revealed three types of glycosaminoglycans, namely, heparan-, chondroitin- and dermatan sulfate, only in the retina. The other eye components contained heparan sulfate and either chondroitin or dermatan sulfate. Tissue autoradiography together with the biochemical techniques contributed to unravel the origin of the glycosaminoglycans in the eye components.Conclusions. The results of the present investigation have shown that heparan sulfate, contrasting to chondroitin sulfate and dermatan sulfate, is synthesized in all eye components studied and that the glycosaminoglycan composition differs according to the tissue of origin.
Keywords: glycosaminoglycans; eye; heparan sulfate; condroitin sulfate; dermatan sulfate; rabbit; rate of synthesis